2009
DOI: 10.1590/s0080-62342009000100012
|View full text |Cite
|
Sign up to set email alerts
|

Perfil das parturientes e seus recém-nascidos atendidos em um hospital-escola do Noroeste do Estado do Paraná

Abstract: The study had the purpose to outline the profile of parturients and their newborn babies receiving care in a school hospital, based on the Live Birth Information System - Sistema de Informações sobre Nascidos Vivos - SINASC. For so, a descriptive, exploratory study was elaborated, identifying the characteristics of all the parturients and their newborns receiving care at Hospital Universitário de Maringá - HUM in 2006. It was observed that 27.1% of the parturients were adolescents, 68.4% had no partner, 59.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2
19

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 11 publications
0
7
2
19
Order By: Relevance
“…15 The prenatal is configured as an essential component of the women's healthcare during pregnancy. 6 Regarding the number of prenatal consultations, seven or more consultations were presented in this study, this was superior to the proportions found by other researchers in studies in the States of São Paulo 12 and Paraná, 16 with 60% and 63.6% of the mothers who had seven or more consultations, respectively. However, despite the number of prenatal consultations offering subsidies to analysis the coverage of this service, it does not necessarily reflect on the quality of healthcare provided at the consultations, thus, the quality and the professionals who attended the patients are unknown, and this fact has already been mentioned by other researchers.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…15 The prenatal is configured as an essential component of the women's healthcare during pregnancy. 6 Regarding the number of prenatal consultations, seven or more consultations were presented in this study, this was superior to the proportions found by other researchers in studies in the States of São Paulo 12 and Paraná, 16 with 60% and 63.6% of the mothers who had seven or more consultations, respectively. However, despite the number of prenatal consultations offering subsidies to analysis the coverage of this service, it does not necessarily reflect on the quality of healthcare provided at the consultations, thus, the quality and the professionals who attended the patients are unknown, and this fact has already been mentioned by other researchers.…”
Section: Discussioncontrasting
confidence: 83%
“…The results found are alarming when compared to the ones observed as in a national level, 43.89% 10 and 53.7%, 17 as in other Brazilian studies [11][12][13]16 which ranged from 31.1% 12 to 56.3%. 13 However, the proportion of cesarean sections found in this study, corroborates with the proportions identified in 2012 and 2013 in the South Region and were circulated recently by the Ministry of Health, 62% and 62.7%, respectively.…”
Section: Factors Associated To Maternal and Child's Health In Rio Gracontrasting
confidence: 58%
See 1 more Smart Citation
“…O Ministério da Saúde classifica os fatores de risco em quatro grandes grupos: características individuais e condições sociodemográficas desfavoráveis; história reprodutiva anterior à gestação atual; doenças obstétricas na gestação atual; e as intercorrências clínicas (4) . Para que haja uma melhor assistência às gestantes, há o interesse em estudar e traçar o perfil das mulheres assistidas, para reconhecer suas individualidades e identificar fatores de risco gestacionais (5) . Dessa forma, o objetivo deste estudo é caracterizar o perfil socioeconômico das gestantes de alto risco atendidas em serviço pré-natal na cidade de Aracaju e compará-las com gestantes de baixo risco.…”
Section: Introductionunclassified
“…A mulher o teme como algo desconhecido, doloroso e também como momento inaugural de concretude da relação mãe-filho; teme também o papel de mãe por este ser mitificado e conter a exigência de a mãe ser um modelo de perfeição. O conhecimento sobre as características obstétricas de parturientes em um determinado local e período é de fundamental importância, para possibilitar a elaboração de indicadores demográficos e epidemiológicos que podem representar a realidade da comunidade para o planejamento e implementação de estratégias efetivas de melhorias das condições de saúde (3) . O acompanhamento à mulher no ciclo gravídico deve ser realizado com o objetivo de garantir o bem estar ao binômio mãe-filho.…”
Section: Introductionunclassified